PROTOTIPE SISTEM MONITORING DAN KONTROL PH SERTA NUTRISI TANAMAN HIDROPONIK BERBASIS IOT UNTUK PERTANIAN - Ariyo Banjardana; Titi Andriani; Paris Ali Topan; Nova Aryanto (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The development of technology in agriculture is increasingly rapid hydroponics which utilizes water as a growing medium requires manual pH and water nutrition settings which are time-consuming and labor-intensive and often ineffective. This research aims to develop a prototype of a real-time monitoring and control system for pH and nutrition of hydroponic plants using IoT. The system is designed using pH and TDS sensors to accurately monitor pH values and water nutrients. sensors are used to control the peristaltic pump operated by ESP32. The reading and control data are displayed on the LCD and mobile device through the Blynk IoT application, as well as sending notifications when changes in pH and water nutrients occur. System testing was carried out in two stages, first with running water conditions, showing that the pH value tends to stabilize between 6.95 to 8.14, while the nutrient value fluctuates more but remains within the required range, second with still water conditions showing better pH stability, but the nutrient value tends to decrease linearly. The results of this study show that the developed prototype can successfully monitor and control pH and nutrients in hydroponic plants efficiently. This system provides a practical solution for hydroponic farmers.